EKONOMI SYARIAH SEBAGAI FONDASI EKONOMI KERAKYATAN : (Analisis UU Nomor 21 Tahun 2008 Tentang Perbankan Syariah) - Yunus, Muhammad; Syahriza, Mulkan (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2025)
Law Number 21 of 2008 concerning Sharia Banking is a statutory regulation that regulates the sharia economy in Indonesia. This law came into force on 16 July 2008. This law regulates: Sharia principles, economic democracy, prudence in sharia banking, sharia bank business licensing, types and business activities of sharia banks, feasibility of channeling funds, controlling shareholders, board of commissioners and directors, sharia supervisory board and governance. In compiling this article, the author used qualitative research using library research. As for the nature of the research, the author uses descriptive research. Before discussing the concrete forms of economic welfare and sharia economics, it is necessary to first know the similarities in the characteristics of the Indonesian economy, namely the people's economy and the sharia economy. The characteristics of popular economics that apply in Indonesia are divinity, humanity, unity, deliberation and social justice. Characteristics of sharia economics: Sourced from God and religion, moderate and balanced economy, sufficient and just economy, and growth and blessing economy.